Pemberdayaan Petani Pala dalam Meningkatkan Produktivitas Hasil Tanaman Pala di Distrik Pariwari Kabupaten Fakfak - Ichlazul Amal Suaery; Bayu Akbar (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2022)
Fakfak Regency is one of the largest nutmeg producers in West Papua. Hence, the authors are interested in conducting this study entitled